2021
DOI: 10.3389/fpls.2021.741415
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and RNA-Sequencing Analysis Show Epigenetic Function During Grain Filling in Foxtail Millet (Setaria italica L.)

Abstract: Grain filling is a crucial process for crop yield and quality. Certain studies already gained insight into the molecular mechanism of grain filling. However, it is unclear whether epigenetic modifications are associated with grain filling in foxtail millet. Global DNA methylation and transcriptome analysis were conducted in foxtail millet spikelets during different stages to interpret the epigenetic effects of the grain filling process. The study employed the whole-genome bisulfite deep sequencing and advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Foxtail millet grain filling progress is crucial for seed setting, grain weight, quality, and yield [39]. This process is highly sophisticated, involving the accumulation of carbohydrates and other nutrients by the developing endosperm to synthesize starch and enhance grain development [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foxtail millet grain filling progress is crucial for seed setting, grain weight, quality, and yield [39]. This process is highly sophisticated, involving the accumulation of carbohydrates and other nutrients by the developing endosperm to synthesize starch and enhance grain development [52].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, clean reads were obtained by filtering out unqualified raw reads, based on Q20, Q30, and GC content criteria. The clean reads were trimmed with Trimmomatic (version 0.36) [41] while HISAT2 (version v2.0.5) [42] mapped them to the reference genome of foxtail millet [39]. Differential expression analysis of genes was performed using the DESeq package with BaseMean value estimation [43].…”
Section: Rna Sequencing and Transcriptomic Profiling Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This mutant resulted in reduced boron with thicker cell walls in Setaria ( Wang et al, 2021b ). DNA methylation studies and transcriptome analysis revealed the role of epigenetic modifications during grain filling ( Wang et al, 2021d ). Recently, RNA-seq analysis of two mutants siaux1-1 and siaux-1-2 was performed to identify auxin-responsive factors beneath C 4 root system architecture in shaping the root apical meristem ( Tang et al, 2022 ).…”
Section: Omics Resources In Setariamentioning
confidence: 99%
“…DNA methylation is an important and conserved epigenetic modification [18] that happens in CG, and CHG contexts (symmetrical), or in CHH contexts (asymmetrical) [19]. DNA methylation has been shown to influence a variety of leaf features, including growth [20], senescence [21], shape [22], and pigmentation [23,24].…”
Section: Introductionmentioning
confidence: 99%